Enteral nutrition supplemented with l-glutamine and its action on the inflammatory process, the glycolytic metabolism, the immune system and the oxidative stress of patients with systemic inflammatory response syndrome - Ana Augusta Monteiro Cavalcante (2010)
The Systemic Inflammatory Response Syndrome (SIRS) is characterized by an excessive release of inflammatory mediators as a systemic inflammatory response to a serious clinical injuries. The use of glutamine in nutraceutical doses has been studied as a strategy in tissue protection and preservative of tissue metabolic function in stressful situations, helping to improve the immune response of patients. The effects of enteral glutamine supplementation in nutraceutical doses on the inflammatory markers, of glycolytic metabolism, of immune system and of oxidative stress were studied in adult and elderly patients with SIRS in a prospective, clinical, randomized, controlled, double-blind crossover study. Thirty six moderately severe patients admitted to the Intensive Care Unit were selected according to pre-defined criteria, diagnosis of SIRS and the APACHE II score (>10<20), distributed into two groups and submitted to the supplementation with 1 litre of enteral nutrition with addition of 30g of L-glutamine or calcium caseinate or 1 litre of enteral nutrition with addition of 30g of calcium caseinate or L-glutamine for two days, pause for one day only with diet, followed by four days of supplementation. Blood samples were collected before (T0) and after (T1) each supplementation. For evaluation blood parameters (hematocrit, leukocytes, lymphocytes, monocytes, prealbumin, blood urea nitrogen, creatinine, glucose, lactate, C-peptide and insulin), IL-1, IL-6, IL-10 and TNFα were also assayed. Glutathione, TBARS, and glutamine and glutamate amino acids were measured. Six patients died during the study. Thirty patients finished the study, 16 men (53%) and 14 (47%) women, median age 74.4 years (30-92 years) in moderately severe state of health (APACHE II 13.1 - range 10-19). All patients developed SIRS and were given enteral nutrition supplemented with L-glutamine or calcium caseinate, 1464kcal/day (range 792-1914kcal/day). The use of L-glutamine in nutraceutical dose of 30g/day showed no changes in blood parameters. All laboratory parameters remained within normal values except the blood urea [Calcium Caseinate T1=47.0mg/dL (range 34.0-69.0 mg/dL) versus Glutamine T1=50.0mg/dL (36.75-75.0mg/dL); p=0.030]. Creatinine concentrations were not statistically different. There was no statistically significant difference in assessment of inflammatory parameters (IL-1, IL-6, IL-10 E TNFα). Leukocytes count decreased significantly in both groups [Calcium Caseinate T0=13.650 1/mm3 (10.148-18.250 1/mm3) versus T1=11.500 1/mm3 (8.050-29.100 1/mm3); p=0,019] and [Glutamine T0=12.850 1/mm3 (11.155-15.550 1/mm3) versus T1=11.000 1/mm3 (9.200-16.325 1/mm3); p=0.046]. There was increase statistically significant difference in lymphocytes count between groups [Calcium Caseinate T1=1085 1/mm3 (range 805-1363 1/mm3) versus Glutamine T1=1916 1/mm3 (1301-2517 l/mm3); p<0.0001] and Calcium Caseinate group decreases [T0=1288 1/mm3 (range 834-2209 1/mm3) versus T1=1085 1/mm3 (range 805-1363 1/mm3); p=0.0324] and Glutamine group increases [T0=954 1/mm3 (range 785-1442 1/mm3) versus T1=1916 1/mm3 (range 1301-2517 l/mm3); p<0.0001]. Blood concentration of TBARS decreased significantly in both groups [Calcium Caseinate T0=20.56mol MDA/ml (range 13.64-20.56mol MDA/ml); p=0.001] and [Glutamine T0=17.67 mol MDA/ml (range 8.11-34.98 mol MDA/ml) versus T1=16.52 mol MDA/ml (range 5.41-21.86 mol MDA/ml); p=0.020]. The blood concentrations of Gluthatione showed a statistically significant reduction in caseinate group (T0=486.0mol/ml (range 486.0Â165.8mol/ml versus T1=451.0Â167.4mol/ml; p=0.047) and no statistically significant difference in the glutamine group, nor between groups. However, there were no differences between groups. Glutamine and glutamate were not statistically different. Enteral nutrition supplemented with glutamine in nutraceutical doses of 30g/day increase lymphocyte count, helps to reduce lipid peroxidation and maintains the antioxidant glutathione capacity, interfering beneficially modulating the inflammatory response and stress, but present no effect upon cytokines concentrations or glycolytic parameters.